2013
DOI: 10.1002/bmc.2993
|View full text |Cite
|
Sign up to set email alerts
|

Combined solid‐phase microextraction and high‐performance liquid chromatography with ultroviolet detection for simultaneous analysis of clenbuterol, salbutamol and ractopamine in pig samples

Abstract: A simple and sensitive method based on the combination of solid-phase microextraction (SPME) and high-performance liquid chromatography with ultroviolet detection was developed for the simultaneous determination of clenbuterol, salbutamol and ractopamine in pig samples. Parameters of the SPME procedure affecting extraction efficiency, such as the type of fiber, extraction time, extraction temperature, ion strength, pH of sample and stirring rate, were optimized. The developed method was validated according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…A number of sample pre‐treatment methods, based on novel adsorbents, have been developed for the analysis of SAL. C 18 ‐SPE (Fiori et al ., ), weak cation exchange columns (Meng et al ., ), molecularly imprinted polymers (Yan et al ., ), polymer microextraction (Huang et al ., ; Du et al ., ), immunoaffinity columns (Wang et al ., ), tert ‐butylmethylether extraction (Garrido et al ., 2013) and poly (MAA‐EGDMA) SPE columns (Wang et al ., ) have been used to extract SAL from the complex biological samples. However, most of these methods are nonspecific and may lead to nonspecific adsorption from the sample matrix.…”
Section: Introductionmentioning
confidence: 99%
“…A number of sample pre‐treatment methods, based on novel adsorbents, have been developed for the analysis of SAL. C 18 ‐SPE (Fiori et al ., ), weak cation exchange columns (Meng et al ., ), molecularly imprinted polymers (Yan et al ., ), polymer microextraction (Huang et al ., ; Du et al ., ), immunoaffinity columns (Wang et al ., ), tert ‐butylmethylether extraction (Garrido et al ., 2013) and poly (MAA‐EGDMA) SPE columns (Wang et al ., ) have been used to extract SAL from the complex biological samples. However, most of these methods are nonspecific and may lead to nonspecific adsorption from the sample matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation was intensified using sonication, as was reported in [12]. It was found that extraction with ultrasonic sample treatment for 10-15 min ensures a higher recovery of analytes from the matrix (from 68-75 to 89-104%).…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantages of the existing techniques of sample preparation are high time consumption (enzymatic or acid hydrolysis takes several hours) and multistage purification of the extract. A possibility of the intensification of sample preparation by sonication in the extraction of β-agonists from biological materials and their subsequent preconcentration by solid-phase microextraction, significantly reducing the time of sample preparation, was demonstrated in [12].…”
mentioning
confidence: 99%
“…Grafting polymerization of MAA onto silica gel particles was conducted by "the grafting from" method [21][22][23] with the help of MPS. Functionalization of silica with MPS provided a polymerizable surface with double bonds, allowing for subsequent formation of PMAA/SiO2 particles.…”
Section: Preparation Of Mipsmentioning
confidence: 99%